Heliophysics and space weather science at ∼1.5 AU: Knowledge gaps and need for space weather monitors at Mars - Lee, Christina O.; Sánchez-Cano, Beatriz; DiBraccio, Gina A.; Mayyasi, Majd; Xu, Shaosui; Chamberlin, Phillip; Davies, Emma; Scolini, Camilla; Filwett, Rachael J.; Ramstad, Robin; Palmerio, Erika; Lynch, Benjamin J.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
This perspective article discusses the knowledge gaps and open questions regarding the solar and interplanetary drivers of space weather conditions experienced at Mars during active and quiescent solar periods, and the need for continuous, routine observations to address them. For both advancing science and as part of the strategic planning for human exploration at Mars by the late-2030s, now is the time to consider a network of upstream space weather monitors at Mars. Our main recommendations for the heliophysics community are: 1. Support the advancement for understanding heliophysics and space weather science at $\sim$1.5 AU and continue support of planetary science payloads and missions that provide such measurements. 2. Prioritize an upstream Mars L1 monitor and/or areostationary orbiters for providing dedicated, continuous observations of solar activity and interplanetary conditions at $\sim$1.5 AU. 3. Establish new or support existing (i) joint efforts between federal agencies and their divisions and (ii) international collaborations to carry out #1 and #2.